La incorporación de ejes transversales en la educación superior: el marco institucional y el acompañamiento como condiciones para el éxito - Claudia Charpentier-Esquivel; Lupita Jiménez-Reyes; Virginia Sánchez-Molina (Universidad Nacional, Costa Rica, 2007)
The National University decided to include five institutional transverse axes in the curricula. In order to be successful, a process was undertaken, that considered two fundamental components: the institutional framework and joint work with professors and departments, as a mean of reducing barriers that could interfere in the inclusion of gender, sustainable development, environment and environmental culture, equity and cultural diversity in curricula. In this paper are included, the institutional framework and the aspects that were considered during the joint work as well as the training provided to faculty and chairpersons during the process.